Bounding the Price Equivalent of Migration Barriers - Michael A. Clemens; Claudio Montenegro; Lant Pritchett (Institute for the Study of Labor (IZA), 2016)
Large international differences in the price of labor can be sustained by differences between workers, or by natural and policy barriers to worker mobility. We use migrant selection theory and evidence to place lower bounds on the ad valorem equivalent of labor mobility barriers to the United States, with unique nationally-representative microdata on both U.S. immigrant workers and workers in their 42 home countries. The average price equivalent of migration barriers in this setting, for low-skill males, is greater than 13,700 per worker per year. Natural and policy barriers may each create annual global losses of trillions of dollars.
Keywords: F22; J61; J71; O15; 330; migration; growth; impact; GDP; tariff; quota; deadweight; cost; visa; barrier; price; wedge